Propuesta de asociatividad para pequeños productores del cantón Paltas, Provincia de Loja - Balcázar Vargas, Danny Manuel (2024)
Globally, the primary sector of the economy, particularly agricultural activity, plays a crucial role in development and food security, contributing approximately 25% of GDP in developing countries. However, Ecuador presents a contrasting reality, with this figure standing at around 8%, which can be attributed, among other factors, to the migration of the rural population driven by the low incomes of small-scale farmers. These limitations hinder significant agricultural contributions compared to other countries. In this context, it is essential to highlight that the agricultural sector supplies national food needs, necessitating its strengthening. Therefore, this research aims to design an associative proposal for small-scale farmers in the Canton of Paltas. A mixed-methods approach was adopted, using surveys to collect data from a sample of 171 small-scale farmers in the Canton of Paltas and conducting interviews with intermediaries. The results show that the main activities are maize and peanut cultivation. In marketing processes, two modes of intermediation were identified: direct and prolonged storage. However, the income earned by small-scale farmers does not compensate for their labor. It is concluded that the most suitable form of association is as a legal entity. The proposed model emphasizes commercialization with prolonged storage, subject to prior agreements with producers, to increase profitability, reduce costs and production expenses, and improve the quality of life for small-scale farmers.